Partisan politics and fiscal policy - Cusack, Thomas R. (1999)
Does the partisan character of governing parties play a role in the formation of fiscal policy? The conventional view is that the left tends toward excessive deficits, whereas the right practices a more prudent fiscal policy; however, strong arguments have been advanced that whatever room existed previously for partisanship in fiscal policy making has been sharply reduced by developments in recent decades. These issues are examined with a series of models that have been estimated using data from 14 Organization for Economic Cooperation and Development countries for the period from 1961 through 1991. The evidence suggests that the relationship between partisanship and fiscal policy is contingent on macroeconomic conditions. The evidence also suggests that these differences have been reduced over recent decades. - Reproduced
Keywords: Fiscal policy